Haunted laughter : representations of Adolf Hitler, the Third Reich, and the Holocaust in comedic film and television /: representations of Adolf Hitler, the Third Reich, and the Holocaust in comedic film and television. (2022) - Friedman, Jonathan C, 1966-
No abstract available